Effect of Mucine 4 and Fucosyltransferase 1 genetic variants on gut homoeostasis of growing healthy pigs. Issue 3 (7th February 2019) - Luise, Diana; Motta, Vincenzo; Bertocchi, Micol; Salvarani, Chiara; Clavenzani, Paolo; Fanelli, Flaminia; Pagotto, Uberto; Bosi, Paolo; Trevisi, Paolo
Abstract: Putative genetic markers have been associated with ETEC F4 (Mucine 4 [ MUC4 ] ; MUC4 GG;CG as susceptible; MUC4 CC as resistant) and F18 (Fucosyltransferase 1 [ FUT1 ] ; FUT1 GG;AG as susceptible; FUT1 AA as resistant) resistances respectively. In this study, 71 post‐weaning pigs were followed from d0 (35 days old) to d42 (77 days of age) to investigate the effect of MUC4 or FUT1 genotypes on the mid‐jejunal microbiota composition, pigs expression of genes related to inflammation ( IL8, GPX2, REG3G, TFF3, CCL20 and LBPI ) and glycomic binding pattern profile (Ulex europaeus agglutinin I [UEA] fucose‐binding lectin and peanut agglutinin [PNA] galactose‐specific), and on blood plasma targeted metabolomics profile, faecal score and performance parameters of growing healthy pigs. The MUC4 and FUT1 resistant genotypes improved the pigs' growth performance and had firmed faecal score susceptible genotypes in d0–d21 period. Pigs with MUC4 GG genotype had a higher jejunal expression of genes relate to immune function ( CCL20 and REG3G) than MUC4 CG and MUC4 CC pigs ( p <  0.05). MUC4 CG pigs had higher expression of TFF3 (implicated in mucosal integrity) than MUC4 GG and MUC4 CC ( p  < 0.05). FUT1 influenced the alpha‐ and beta‐jejunal microbial indices. The FUT1 AA group had a higher number of operational taxonomic units (OTUs) belonging to Lactobacillus genus, while FUT1 GG group had a higher number of OTUs belonging to Veillonella genus . MUC4 CC pigs had lower scores for UEA on brush borders and goblet cells in villi than MUC4 GG ( p  < 0.05). FUT1 AA pigs had lower UEA positivity and higher PNA positivity on brush borders and goblet cells than FUT1 AG and FUT1 GG ( p  < 0.05). Both FUT1 and MUC4 influenced the metabolic profile of healthy pigs. Results highlight the role of MUC4 and FUT1 on pig intestinal homoeostasis and improved the knowledge regarding the potential interaction between host genetics, gut microbiota composition and host metabolism in a healthy status.